Vygotsky's Theory: reflections on the use of virtual learning environment and Problem Solving in Chemistry Teaching (Research, Society and Development, 2021)
For chemistry teaching and other areas of knowledge, several active methodologies can be applied, in view of the students' learning process, reinforcing a proactive behavior in the search for the construction of knowledge. In this aspect, the figure of Vygotsky emerges and the contemporaneity of his theory influencing Education with regard to the relationship of the individual and its social and cultural context. Thus, the purpose of this study is to bring a reflection on Vygotsky's theory in the use of problem solving teaching methodology in a Virtual Learning Environment in the area of Chemistry Teaching. The methodology used was a bibliographic framework of articles and the results indicate that interactionism contributes satisfactorily to the discussions involved in pedagogical processes. It can also be pointed out that the Problem Solving methodology implemented through a Virtual Learning Environment is a challenging strategy to teach Chemistry in a way that students can understand the problems and interpret it using the Virtual Learning Environment to dialogue with their colleagues and teachers about the solutions of a given situation.